Comparison of phenobarbitone and ursodeoxycholic acid in drug-augmented hepatobiliary scintigraphy for excluding the diagnosis of obstructive cholestasis in neonatal cholestasis syndrome. Issue 8 (August 2015) - Malik, Dharmender; Khan, Shoukat H.; Ali, Syed W.; Rather, Tanveer A.; Pakala, Rammanohar; Hassan, Masood Ul; Yadav, Naveen; Pasupula, Madhuvijay
<x xml:space="preserve">Abstract</x> Objectives Neonatal cholestasis is a common cause of jaundice among newborns. Hepatobiliary scintigraphy plays an important role in the diagnosis of neonatal cholestasis by ruling out extrahepatic biliary atresia, which is one of the common causes. Phenobarbitone and ursodeoxycholic acid (UDCA) have been used to improve the specificity of hepatobiliary scintigraphy in ruling out obstructive causes of neonatal cholestasis syndrome (NCS). The present study was undertaken to compare the utility of phenobarbitone and UDCA in augmenting hepatobiliary scintigraphy in the evaluation of NCS. Materials and methods Seventy-four consecutive patients with NCS referred for hepatobiliary scintigraphy were initially subjected to a baseline scan. Twenty patients showed tracer activity in the intestine within 24 h after injection, thus ruling out obstructive cholestasis. Fifty-four patients who did not show any tracer activity in the intestine were categorized as nonexcretors. Four nonexcretors were lost to follow-up and were excluded from the study. Fifty nonexcretors showing scan features suggestive of obstructive cholestasis were further randomized into those receiving phenobarbitone (n=20), UDCA (n=20), or placebo (n=10). These groups were further evaluated with drug-augmented hepatobiliary scintigraphy, after premedication, for any excretory activity in the intestine. Results and conclusion Out of 50 patients who were evaluated with drug-augmented hepatobiliary scintigraphy two patients from the phenobarbitone group and one patient each from UDCA and placebo groups showed a change in excretory pattern from the baseline scan. However, these results were statistically nonsignificant (P=1.00). In the present study, drug-augmented (phenobarbitone or UDCA) hepatobiliary scintigraphy did not seem to improve the results (negative predictive value) for ruling out an obstructive cause of neonatal cholestasis.